Follicular thyroid carcinoma in dogs. Report of cases - de Nardi, A. B.; Daleck, C. R. [UNESP]; Silva, M. C. V. [UNESP]; Canola, J. C. [UNESP]; Dias, L. G. G. G. [UNESP]; Calazans, Sabryna Gouveia [UNESP]; Fernandes, S. C. [UNESP]; Eurides, D.; Silva, L. A. F.; Huppes, R. R. (Univ Austral Chile, Fac Ciencias Veterinarias, 2011)
The treatment of choice for these cases was surgical removal. In both cases the diagnostic was infiltrative follicular carcinoma of thyroid. The first animal did not present a good recovery after the surgery, and died four hours after the procedure. In the second case, the diagnosis was more precocious and antineoplastic chemotherapy was used after the surgery. At the time of submission of this manuscript, this animal had survived for foully months. Currently, there is a need to define the protocols of chemotherapy to avoid relapse and metastases, in order to increase the life expectancy in dogs with thyroid neoplasm.

El presente trabajo tiene como objetivo relatar la ocurrencia de dos casos de neoplasia de tiroides en perros. El tratamiento de elección para estos casos fue exéresis quirúrgica. En ambos casos el diagnóstico fue carcinoma folicular infiltrativo de tiroides. El primer animal no presentó buena recuperación posquirúrgica, y murió cuatro horas después del término de la cirugía. En el segundo caso el diagnóstico fue más precoz y después de la cirugía se asoció el uso de la quimioterapia antineoplásica. Hasta el momento, este animal presenta cuarenta meses de supervivencia. Actualmente, existe la necesidad de definir protocolos quimioterapéuticos más eficaces para evitar la ocurrencia de recidivas y metástasis, aumentando la expectativa de vida de los perros con neoplasia tiroidea. The aim of this study was to report the occurrence of two cases of thyroid neoplasm in dogs.
Follicular thyroid carcinoma in dogs. Report of cases
Keywords: Neoplasia; thyroid; follicular carcinoma; Dog